Poria cocos polysaccharides exert prebiotic function to attenuate the adverse effects and improve the therapeutic outcome of 5-FU in Apc Min/+ mice - Lin Yin; Guoxin Huang; Imran Khan; Lu Su; Wenrui Xia; Betty Yuen Kwan Law; Vincent Kam Wai Wong; Qiang Wu; Jingyi Wang; Wai Kit Leong; W. L. Wendy Hsiao (BMC, 2022)
Abstract Background As a first-line chemotherapeutic agent, 5-fluorouracil (5-FU) exhibits many side effects, weakening its efficacy in cancer treatment. In this study, we hypothesize that Poria cocos polysaccharides (PCP), a traditional Chinese herbal medicine with various bioactivities and prebiotic effects, might improve the therapeutic effect of 5-FU by restoring the homeostasis of the gut microenvironment and the commensal gut microflora. Methods Apc Min/+ mice were employed to evaluate the anti-cancer effect of 5-FU in conjunction with PCP treatment. Body weight and food consumption were monitored weekly. Polyp count was used to assess the anti-cancer effect of PCP and 5-FU. Expressions of mucosal cytokines and gut epithelial junction molecules were measured using qRT-PCR. 16S rRNA gene sequencing of fecal DNAs was used to evaluate the compositional changes of gut microbiota (GM). Transplantation of Lactobacillus johnsonii and Bifidobacterium animalis were performed to verify the prebiotic effects of PCP in improving the efficacy of 5-FU. Results The results showed that PCP treatment alleviated the weight loss caused by 5-FU treatment and reduced the polyp burden in Apc Min/+ mice. Additionally, PCP treatment eased the cytotoxic effects of 5-FU by reducing the expressions of pro-inflammatory cytokines, increasing the anti-inflammatory cytokines; and significantly improving the gut barriers by enhancing the tight junction proteins and associated adhesion molecules. Furthermore, 16S rRNA gene sequencing data showed that PCP alone or with 5-FU could stimulate the growth of probiotic bacteria (Bacteroides acidifaciens, Bacteroides intestinihominis, Butyricicoccus pullicaecorum, and the genera Lactobacillus, Bifidobacterium, Eubacterium). At the same time, it inhibited the growth of potential pathogens (e.g., Alistipes finegoldii, Alistipes massiliensis, Alistipes putredinis., Citrobacter spp., Desulfovibrio spp., and Desulfovibrio desulfuricans). Moreover, the results showed that transplantation of L.johnsonii and B.animalis effectively reduced the polyp burden in Apc Min/+ mice being treated with 5-FU. Conclusion Our study showed that PCP could effectively improve the anti-cancer effect of 5-FU by attenuating its side effects, modulating intestinal inflammation, improving the gut epithelial barrier, and modulating the gut microbiota of ApcMin/+ mice.